2015
DOI: 10.1186/s12974-015-0404-7
|View full text |Cite
|
Sign up to set email alerts
|

The expression levels of prolyl oligopeptidase responds not only to neuroinflammation but also to systemic inflammation upon liver failure in rat models and cirrhotic patients

Abstract: BackgroundLiver failure in experimental animals or in human cirrhosis elicits neuroinflammation. Prolyl oligopeptidase (PREP) has been implicated in neuroinflammatory events in neurodegenerative diseases: PREP protein levels are increased in brain glial cells upon neuroinflammatory insults, but the circulating PREP activity levels are decreased in multiple sclerosis patients in a process probably mediated by bioactive peptides. In this work, we studied the variation of PREP levels upon liver failure and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Elevated PREP activity has also been detected in the sputum of cystic fibrosis patients and knee synovial fluid of patients with rheumatoid arthritis . Pre‐clinically, extracellular brain PREP activity has been identified in a rat model of neuroinflammation . Thus, the present study raises the possibility that the increased extracellular PREP activity observed in these pathological conditions did originate from the immune cells at the site of inflammation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Elevated PREP activity has also been detected in the sputum of cystic fibrosis patients and knee synovial fluid of patients with rheumatoid arthritis . Pre‐clinically, extracellular brain PREP activity has been identified in a rat model of neuroinflammation . Thus, the present study raises the possibility that the increased extracellular PREP activity observed in these pathological conditions did originate from the immune cells at the site of inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…24 Pre-clinically, extracellular brain PREP activity has been identified in a rat model of neuroinflammation. 18 Thus, the present study raises the possibility that the increased extracellular PREP activity observed in these pathological conditions did originate from the immune cells at the site of inflammation. It remains to be clarified why extracellular PREP activity increases specifically in microglial cells during inflammation, but PREP appears to play a role in microglia activation, as PREP knockout mice show a lack of response to LPS at both behavioural and immunohistochemical levels.…”
Section: Discussionmentioning
confidence: 60%
“…Cirrhosis is associated with dysbiosis or an altered gut microbiota that potentiates a systemic proinflammatory milieu . This inflammatory environment can potentiate neuroinflammation and brain dysfunction in the setting of hyperammonemia . However, the specific contribution of the gut microbiota toward neuroinflammation and hyperammonemia in cirrhosis is unclear given that ammonia production can also occur through intestinal glutaminase activity in germ‐free (GF) animals .…”
mentioning
confidence: 99%
“…activity in the plasma of rats with rotenone-induced Parkinson's disease to the level representative for intact rats [47]. The activity of the enzyme is known to correlate with the level of proinflammatory interleukins in rat models and in cirrhotic patients [48].…”
Section: Discussionmentioning
confidence: 99%